(untitled) (Global Journals of Research in Engineering, 2023)
Dynamic adsorption kinetics results indicated that monoethanolamine-carbon dioxide MEA-CO2 reaction in fixed bed column packed with MEA-impregnated activated carbon AC particles is pseudo first order reaction The controlling step slow step of adsorption is the mass transfer of CO2 molecules form the feed gas bulk stream to the surface of the adsorbent through the boundary layer external diffusion A Dubinin-Astakhov and Avrami models showed that adsorption of CO2 on MEA-impregnated activated carbon particles is homogeneous The suggested mass balance model exhibited good agreement with the experimental results for both MEA-impregnated and non-impregnated AC which they show also that there is no difference in adsorption rates between the two adsorption beds